Analisis Penggunaan Bahasa Daerah Pada Proses Pembelajaran di TK Negeri 2 Gunungsari Lombok Barat - Hipziana (Indonesian Journal of Elementary and Childhood Education, 2025)
Language is a communication tool used in everyday life. Apart from using Indonesian in the learning process, regional languages ??are also often used. As is the case at TK Negeri 2 Gunungsari, regional languages ??are still used to create an effective and enjoyable learning atmosphere so that students can more easily understand the material presented by the teacher and they can communicate fluently without any language-related barriers to the theme. And using regional languages ??can regenerate a sense of love for regional languages. This research aims to determine the use of regional languages ??in the learning process. This type of research is qualitative research. The subjects in this research were homeroom teachers. The data collection technique used was random and spontaneous interviews. The results of the research found that children and teachers still often use regional languages ??to communicate so that learning is more effective and easier for participants to understand. Regional languages ??are often used when communicating with teachers, family and pee.